A critical review of virtual and augmented reality (VR/AR) applications in construction safety - Li, X.; Yi, W.; Chi, Hung-Lin; Wang, X.; Chan, A. (Elsevier BV, 2018)
Construction is a high hazard industry which involves many factors that are potentially dangerous to workers. Safety has always been advocated by many construction companies, and they have been working hard to make sure their employees are protected from fatalities and injuries. With the advent of Virtual and Augmented Reality (VR/AR), there has been a witnessed trend of capitalizing on sophisticated immersive VR/AR applications to create forgiving environments for visualizing complex workplace situations, building up risk-preventive knowledge and undergoing training. To better understand the state-of-the-art of VR/AR applications in construction safety (VR/AR-CS) and from which to uncover the related issues and propose possible improvements, this paper starts with a review and synthesis of research evidence for several VR/AR prototypes, products and the related training and evaluation paradigms. Predicated upon a wide range of well-acknowledged scholarly journals, this paper comes up with a generic taxonomy consisting of VR/AR technology characteristics, application domains, safety scenarios and evaluation methods. According to this taxonomy, a number of technical features and types that could be implemented in the context of construction safety enhancement are derived and further elaborated, while significant application domains and trends regarding the VR/AR-CS research are generalized, i.e., hazards recognition and identification, safety training and education, safety instruction and inspection, and so on. Last but not least, this study sets forth a list of gaps derived from the in-depth review and comes up with the prospective research works. It is envisioned that the outcomes of this paper could assist both researchers and industrial practitioners with appreciating the research and practice frontier of VR/AR-CS and soliciting the latest VR/AR applications.